GENERAL DESCRIPTION OF CRITERIA FOR DIVIDING REPRESENTATION INTO TYPES IN CIVIL LAW (TAMADDUN NURI JURNALI, 2024)
This article covers the types of representation in civil law, the criteria for division and methods of protection, solving problems related to participation in social, property and family relations.